2009
DOI: 10.13031/2013.29210
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and Bacterial Transport in Runoff from Soil and Pond Ash Amended Feedlot Surfaces

Abstract: ABSTRACT. The addition of pond ash (fly ash that has been placed in evaporative ponds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…transport in runoff from land application areas to be 12.63 and 12.70 log CFU per 100 mL, respectively (table 1). These values are over one log scale less than measurements obtained by Gilley et al (2008aGilley et al ( , 2009.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…transport in runoff from land application areas to be 12.63 and 12.70 log CFU per 100 mL, respectively (table 1). These values are over one log scale less than measurements obtained by Gilley et al (2008aGilley et al ( , 2009.…”
mentioning
confidence: 57%
“…Mean transport rates of 10.6 log PFU ha -1 , 11.3 log CFU ha -1 , 12.3 log CFU ha -1 , and 11.2 log CFU ha -1 were measured in the present study for phages, total coliforms, E. coli, and enterococci, respectively, on the plots with no wheat strip. Gilley et al (2008aGilley et al ( , 2009) determined the mean transport of E. coli from feedlot surfaces to be 14.0 log CFU ha -1 . When the beef cattle manure was land-applied, the transport rate for E. coli was reduced to 12.6 log CFU ha -1 .…”
Section: Correlation Between Microbial Transport and Runoff Charactermentioning
confidence: 99%
“…The largest number of pathogens in runoff would be expected immediately after land application. Previous studies have been conducted to measure pathogen transport from feedlot surfaces (Gilley et al, 2008(Gilley et al, , 2009 and from land application sites immediately after manure addition (Durso et al, 2011;Thurston-Enriquez et al, 2005).…”
Section: Plot Preparationmentioning
confidence: 99%
“…Clark et al (1975b) reported that the mean slope of selected feedlots in the southern Great Plains ranged from 1.3% near Pratt, Kansas, to 9.0% near Mead, Nebraska. Gilley et al (2009) conducted tests on a feedlot near Clay Center, Nebraska, that had a mean slope of 4.8%. The mean slope of the study site used in this investigation was 5.1%.…”
Section: Study Site Characteristicsmentioning
confidence: 99%